(untitled) (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Different techniques of postsurgical dressings are used after a below-knee amputation (BKA). This study compares the application of soft dressings versus rigid dressings on healing time and hospital stay after BKA. Methods: In this cross sectional prospective analysis of outcome of two types of post-operative dressings after BKA during January 2012 to January 2018 at Shree Bhawani Hospital Birgunj, Nepal. Wound healing time and hospitalisation were compared between soft and rigid dressings. Results: Out of 37 BKA, 20 received soft dressings with knee immobiliser and 17 rigid plaster dressings. Average age of patients in soft dressing group was 41 years (range 10-70) and in plaster dressing group 37.7 years (range 10-70). Two out of 20 (10%) with soft dressing and 13 out of 18 (76.47%) with the rigid dressing healed primarily, p <0.001. Patients treated with soft dressings stayed in the hospital on an average of 35.2 days (range 22-49 days) and rigid dressings 18.4 days (range12-31 days). Conclusions: The patients with rigid dressings after BKA had significantly more primary wound healings and shorter length of hospitalisation compared to soft dressing.